Pengaruh disiplin dan motivasi kerja terhadap kinerja penyuluh agama Islam Non PNS di Kabupaten PALI - Antoni, Antoni; Maulana, Maulana; Wulandari, Novita (Journal of Law & Policy Review, 2024)
This article or writing aims to examine and analyze the influence of discipline and work motivation, both partially and simultaneously, on the performance of non-PNS Islamic religious instructors in the PALI Regency. Data was collected through questionnaires, observation, and documentation, data analysis techniques used were multiple linear regression. The research results show that discipline and work motivation influence the performance of non-PNS Islamic religious instructors in the PALI Regency. Discipline, with an R² value of 0.894, explains 89.4% of the variation in performance, while work motivation is more dominant with an R² value of 0.981, explaining 98.1% of the variation in performance. Work motivation makes a more significant contribution than scientific discipline. To improve the performance of extension workers, it is important to focus on increasing motivation through rewards and support, as well as improving time management and cost management. The PALI Regency Ministry of Religion applies an effective motivational approach, combining intrinsic motivation through training and guidance, as well as extrinsic motivation through honor, uniforms and awards. This approach is expected to improve the performance, job satisfaction and contribution of instructors in religious education.